1999
DOI: 10.1016/s0014-5793(99)01428-3
|View full text |Cite
|
Sign up to set email alerts
|

ATPase activity of the heat shock protein Hsp72 is dispensable for its effects on dephosphorylation of stress kinase JNK and on heat‐induced apoptosis

Abstract: A major inducible heat shock protein, Hsp72, has previously been found to stimulate dephosphorylation (inactivation) of stress kinase JNK in heat-shocked cells and protect them from apoptosis. Using Rat-1 fibroblasts with constitutive expression of a human Hsp72 or its deletion mutant lacking an ATPase domain (C-terminal fragment (CTF)), we tested whether ATPase activity of Hsp72 is necessary for these effects. We found that expression of CTF markedly increased, similarly to the intact protein, JNK dephosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
5
30
0
1
Order By: Relevance
“…In agreement with studies by Li et al and Volloch et al, our results clearly show that Hsp72 protects cells from heatinduced apoptosis and heat-induced protein damage by distinctly different mechanisms (Li et al 1995;Volloch et al 1999). While the repair of heat-denatured luciferase required the chaperone activity of wild-type Hsp72, the substrate-binding domain of Hsp72 was sufficient to inhibit heat-induced apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with studies by Li et al and Volloch et al, our results clearly show that Hsp72 protects cells from heatinduced apoptosis and heat-induced protein damage by distinctly different mechanisms (Li et al 1995;Volloch et al 1999). While the repair of heat-denatured luciferase required the chaperone activity of wild-type Hsp72, the substrate-binding domain of Hsp72 was sufficient to inhibit heat-induced apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed that the Hsp72 substrate-binding domain is sufficient to inhibit heat-induced apoptosis in L929.3 cells as described previously in Rat-1 fibroblasts (Volloch et al 1999). Both the 381-640 Δ-ATPase mutant and the K71E point mutant protected cells in an equivalent fashion to the full length protein, while cells expressing the 1-611 fragment, lacking an active substrate-binding domain, apoptosed at an equivalent rate to base vector control cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations